Mental Aspects Factor of Personal Financial Performance - Mukhtar (PT Larva Wijaya Penerbit, 2025)
This study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the complex interrelationships dimension among money attitudes, spiritual well-being, and personal financial performance of randomly Banten Province adult individuals. The analysis reveals dimension-specific effects: Financial Literacy Worries show negative direct impacts on Personal Financial Performance, and Achievement-Success orientation shows positive direct impacts on Personal Financial Performance. In contrast, Mindful Responsibility demonstrates a substantial positive association with Religious Well-Being, while Saving Concerns positively correlates with Existential Well-Being. Although spiritual well-being measures do not exhibit significant mediating effects, the model demonstrates strong explanatory power (R²). Predictive performance analysis indicates the model's superiority over linear benchmarks. These findings highlight the nuanced, dimension-dependent nature of monetary attitudes while questioning conventional assumptions about spiritual well-being's mediating role in financial outcomes. The results suggest that while conscientious financial behaviors enhance spiritual well-being, financial anxiety, and achievement orientation directly influence financial performance. By empirically validating differential effects across money attitude dimensions and clarifying the limited role of spiritual factors in financial outcomes, this research contributes significantly to behavioral finance literature. Keywords: Spiritual Well-Being, Money Attitudes, Personal Financial Performance